Income contingent loans : theory, practice and prospects - Chapman, Bruce; Higgins, Timothy; Stiglitz, Joseph E.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This study explores the prospect of the application of the basic principles of ICL into many other potential areas of social and economic policy. Using case studies it evaluates previously implemented ICL schemes where interest rate subsidies are usually the norm, and questions the merits of this approach.
Keywords: Science